Cloud computing model selection for e-commerce enterprises using a new 2-tuple fuzzy linguistic decision-making method - Sohaib, Osama; Naderpour, Mohsen; Hussain, Walayat; Martinez, Luis (Computers & industrial engineering, 2019)
•A cloud computing model adaptation for e-commerce is presented.•A novel 2-tuple fuzzy linguistic group decision making model is proposed.•A technology-organization-environment framework is relied upon to determine criteria.•The results show SaaS is the best choice for small and medium-sized e-commerce businesses. Cloud computing is truly transforming the way e-commerce firms do business. While there has been a sharp increase in the use of cloud computing in e-commerce, the benefits of cloud service models have yet to be explored, particularly for small-to-medium-sized businesses. A strong e-commerce offering depends on a reliable and secure online store, therefore it is important for decision makers to adopt the optimal cloud computing service model such as software-as-a-service (SaaS), platform-as-a-service (PaaS), or infrastructure-as-a-service (IaaS), which is a multi-criteria decision-making problem (MCDM). To address this MCDM problem, we propose a novel 2-tuple fuzzy linguistic multi-criteria group decision-making method based on the technique for order preference by similarity to ideal solution (TOPSIS) and rely upon a technology-organization-environment (TOE) framework to determine a set of appropriate criteria. The proposed methodology is applied to a small-to-medium-sized company to facilitate assessing the factors associated with cloud-based e-commerce and making the decision. The result analysis indicates that SaaS is the best choice for small and medium-sized e-commerce businesses considering criteria such as complexity, reliability, security and privacy, organization readiness and firm size, while the selection of PaaS or IaaS can be reinforced considering their compatibility and scalability.